Beiträge zur wogulischen Folklore und Dialektenkunde. - Kannisto, Artturi, 1874-1943. ([Helsingfors, 1908)
Offprint from Finnisch-Ugrische Forschungen, Bd. 8, Hft. 3. Includes bibliographical references. Mode of access: Internet.